Simple and Rapid Determination of Zafirlukast in Plasma by Ultra-performance Liquid Chromatography Tandem Mass Spectrometric Method: Application into Pharmacokinetic Study in Rabbits - Iqbal, M.; Ezzeldin, E.; Al-Rashood, K. A.; Al-khamees, K. I.; Khan, R. M. A.; Raish, M.; Anwer, T. (Drug Research, 2014)
Zafirlukast is a selective leukotriene receptor antagonist used for the prophylaxis and chronic treatment of asthma. The aim of the present study was to develop a simple sensitive ultra-performance liquid chromatography tandem mass spectroscopy method for rapid determination of zafirlukast in plasma. After a simple one step protein precipitation by acetonitrile, zafirlukast and montelukast (IS) were separated on Acquity UPLC BEHTM C18 column (50×2.1 mm, i.d. 1.7 µm, Waters, USA) using a mobile phase of acetonitrile:water containing 10 mM acetic acid (80:20, v/v) at a flow rate of 0.3 mL/min. Zafirlukast and IS were eluted at 0.51 and 1.1 min, respectively with a total run time of only 1.5 min. The mass spectrometric determination was carried out using an electrospray interface operated in the negative mode with multiple reactions monitoring mode. The precursor to product ion transitions of m/z 574.11>462.07 and m/z 584.2>472.1 were used to quantify zafirlukast and IS, respectively. The method was linear in the concentration range of 0.17–600 ng/mL with coefficients of determination greater than 0.996 and lower limit of quantitation of 0.17 ng/mL. Intra-day and inter-day accuracies were 88.3–113.9% and the precisions were ≤12.6%. Zafirlukast was found to stable under various storage and sample processing conditions as per guidelines of bio-analytical method validation. The method developed herein is simple and rapid, and was successfully applied for the pharmacokinetic study in rabbits.
Keywords: zafirlukast; ultra performance liquid chromatography; tandem mass spectrometry; pharmacokinetics; high throughput analysis